2019
DOI: 10.1016/j.pedn.2019.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Parents Experiences Raising a Child with Food Allergy; A Qualitative Review

Abstract: Problem: Food allergies are one of the fastest growing public health concerns without a cure, affecting approximately 8% of the world's child population. Being the parent of a child with allergies may lead to concerns, and affect everyday life in the family. The aim was to synthesize and describe parents' experiences of living with food allergies in families when one of the children has a food allergy. Eligibility criteria: A systematic search using subject terms and text words was performed in Cinahl (Ebsco),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 50 publications
3
15
0
5
Order By: Relevance
“…Although many of the main concepts described here have been reported previously in food allergy studies, it is important that these are confirmed specifically for PA 21,22 . Previous qualitative research documented caregivers’ fear and hesitation related to AAI use, 21 which was also reported by teenagers and caregivers in the current study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although many of the main concepts described here have been reported previously in food allergy studies, it is important that these are confirmed specifically for PA 21,22 . Previous qualitative research documented caregivers’ fear and hesitation related to AAI use, 21 which was also reported by teenagers and caregivers in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…These include the burden of meal preparation, ensuring the home is nut-free, 9 and difficulties with teenagers' transitions to independence and the diminishment of caregiver control. 10,21 Although many of the main concepts described here have been reported previously in food allergy studies, it is important that these are confirmed specifically for PA. 21,22 Previous qualitative research documented caregivers' fear and hesitation related to AAI use, 21 which was also reported by teenagers and caregivers in the current study. A large qualitative study of food allergy The absence of such a link may be due to a reduction in uncertainty when a reaction is experienced and is successfully managed, 23 or to other moderators, such as levels of social support and awareness.…”
Section: F I G U R Esupporting
confidence: 70%
“…• Fear of accidental exposure: uncertainty, anxiety and distress in parents, children [1][2][3] and adolescents. 4 5 Survey: more than 50% of 853 US parents of children with peanut allergy reported to be always afraid of exposure.…”
Section: Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…The current standard management for food allergy is complete avoidance of the offending allergen in the diet, combined with training on how to recognize and treat allergic reactions. And while avoidance is currently recognized as a safe approach, it has a limited ability to improve a patients' perception of safety or sense of control over the condition and its associated limitations-this leads many to seek alternative management options [1][2][3][4][5][6]. Oral immunotherapy (OIT) consists of daily ingestion of the offending food allergen (food dosing), starting below a patient's threshold dose (i.e.…”
mentioning
confidence: 99%
“…This can also affect daily family activities in children with food allergies, as in our study, where the age of the child affects daily family activities, especially due to increasing age, such as teenagers with food allergies. They have a lower and narrower risk perception, and they seem to care less about their condition that one day can cause an allergic reaction due to the consumption of food freely [ 32 , 33 ]. The desire to be independent causes teenagers to take risks even though they realize the consequences and they are annoyed with parents who often worry and control their lives [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%